(untitled) (Homoeopathy for All, 2024)
Urinary tract infections (UTI) are among the most prevalent infectious GLVHDVHV ZLWK D VXEVWDQWLDO ¿QDQFLDO burden on society. These are among the most common bacterial infections in humans, both in the community and hospital settings and have been reported in all age groups in both sexes. A case series of 4 patients diagnosed with UTI with history of recurrence/incomplete relief after conventional treatment and complete resolution in response to homoeopathic medicine Prunus spinosa is presented.